P0316RELATION OF RENAL ULTRASONOGRAPHIC MEASUREMENTS WITH BODY HEIGHT. (6th June 2020) - Spasovska Vasilova, Adrijana; Trajcheska, Lada; Milenkova, Mimoza; Canevska, Aleksandra; Kabova, Angela; Stojanoska, Ana; Pushevski, Vladimir; Rambabova Bushljetikj, Irena; Nikolov, Igor; Severova- Andreevska, Galina; Pavleska Kuzmanoska, Svetlana; Petronijevic, Dzvezdana; et al.
Abstract: Background and Aims: Kidney size has been found to be correlated with anthropometric features and is different among different ethnicities. In this study, we used ultrasonography for measurement of kidney volumes in healthy individuals and evaluated the relationships with body height, age and gender. Method: We conducted a cross-sectional observational study and evaluated 108 healthy individuals whose serum creatinine level was within reference range. Patients' medical clinical and laboratory records were reviewed. Age, gender and height were recorded. Pearson correlation coefficients were used to evaluate the strength of association between ultrasonographic parameters with each other and with other parameters, and were expressed as r 2 . Variations in left and right renal dimensions between various age groups were compared using a one-way analysis of variance, followed by a post-hoc Tukey's test. Results: Subjects' age ranged from 16 to 84 years and the mean age was over 50 years. There was an equal distribution among genders. Strong and positive correlations were seen for the measured length, parenchyma thickness and also for both total and parenchymal volumes with subjects' height for both kidneys. The strongest correlations were observed for the left and right kidney length and also for the right kidney parenchymal volume (r=0.536, p=0.001; r=0.469, p=0.001; r=0.44, p=0.001). On the opposite, most of the relations with age were negative, but week and insignificant. When we divided the study subjects into three age groups and compared them for the height, there was no significant difference among them. Regarding the parenchymal and total kidney volumes of both kidneys, the different age groups showed similar findings in the ultrasonographic measurements. The mean calculated volumes were slightly declining with age and showed the largest values in the first group of patients under 30 years and lowest values in patients over 70 years old. Ultrasonographic measurements were also compared among the two genders. Both (men and women) showed similar age (53.55 ± 18.22 vs. 50.79 ± 18.13 p= 0.430, respectively). As for the height, men were significantly taller than women (1.734 ± 0.007 vs. 1.637 ± 0.005, p= 0.001). The kidney length, volume and parenchymal volumes of both kidneys were significantly larger in men. Conclusion: Renal length and volume are strongly correlated with body height. This relation must be considered in clinical decisions on further investigations regarding kidney disease progression.